ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER PADA NOVEL “9 MATAHARI” KARYA ADENITA - Muthia Hasna Harmanti (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The novel is one of the literary works written by the author based on oneself or the experiences of others. Novels are liked by many people because there are moral values that are useful for daily life. The moral value is related to character education which has always been considered important for social life. Character education is often considered trivial because the delivery is not as clear as the delivery of formal education. In the novel "9 Matahari" adenita's work contains a lot of values of character education that can change the behavior of readers for the better. This study aims to describe the values of character education in the novel "9 Matahari" by Adenita. The method used is descriptive qualitative. The object of research is the novel "9 Matahari" by Adenita. Data collection techniques by finding data in the form of novels, the second stage of perusing each line of the novel, the third stage of collecting data by searching and marking fragments containing character values, the fourth stage codes the fragments of novels that contain character values, the fifth stage classifies and describes novel character values, the sixth stage by concluding the analysis of the character values in the novel. Data analysis was performed by researchers, namely content analysis. Conclusions are deductive or inductive. The results of this study show ten values of character education contained in the novel "9 Matahari" by Adenita namely (1) religious values, (2) honest values, (3) values of hard work, (4) reading values, (5) the value of responsibility, (6) independent, (7) curiosity, (8) discipline, (9) the value of social care, and (10) the value of friendly / communicative.